Foreign Policy Involvement Matters: Towards an Analytical Framework Examining the Role of the Media in the Making of Foreign Policy - Schulz, Kerstin (Global Media Journal - German Edition, 2013)
Foreign policy processes have long played a minor role in the study of political communication. There is a broad consensus that the media is the central mediating actor and primary conduit between political decision-makers and the public. However, the media’s influence on foreign policy remains contingent across various processes and phases of foreign policy making; it is dynamic and multi-directional. Considering that the public sphere is essential for the legitimacy of foreign policy making, there is a demand for further research on the media’s performance in the making of foreign policy. Based on secondary research, this paper proposes an analytical framework for the systematic analysis of media–foreign policy relations by integrating foreign-policy context conditions as a research variable. The framework is based on the assumption that the role of the media varies across diverse foreign policy contexts depending on the intensity of governmental involvement in foreign affairs. The intensity is distinguished according to three dimensions: no involvement, indirect involvement and direct involvement. Finally, a case study is suggested in order to demonstrate the framework’s explanatory power: the German media coverage of Russia.